Diariusze i ich czytelnicy. O narracyjnych aspektach pamiętnikarskich relacji z poselstwa Wojciecha Miaskowskiego do Turcji w 1640 roku - Bauer, Marcin (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2012)
Article compares (in certain aspects of narration) three diaries written in 1640 during chamberlain of Lvov Wojciech Miaskowski's voyage to Turkey, where he was sent by the king Vladislaus IV Vasa as an envoy to the sultan Ibrahim I. An overview of different ways of presenting the same events by different authors shows the development of old Polish diaries as a quasi-literary genre, in particular the noticeable tendency to fictionalize the story, regardless of the addressees of the text. Analyzed relations indicate the presence of this trend in both official and private diaries.